Examining Methods for Combining Speed and Accuracy in a Go/No-Go Vigilance Task. (December 2020) - Mueller, Shane T.; Alam, Lamia; Funke, Gregory J.; Linja, Anne; Ibne Mamun, Tauseef; Smith, Samantha L.
In many human performance tasks, researchers assess performance by measuring both accuracy and response time. A number of theoretical and practical approaches have been proposed to obtain a single performance value that combines these measures, with varying degrees of success. In this report, we examine data from a common paradigm used in applied human factors assessment: a go/no-go vigilance task (Smith et al., 2019). We examined whether 12 different measures of performance were sensitive to the vigilance decrement induced by the design, and also examined how the different measures were correlated. Results suggest that most combined measures were slight improvements over accuracy or response time alone, with the most sensitive and representative result coming from the Linear Ballistic Accumulator model. Practical lessons for applying these measures are discussed.